Evaluation of an Innovative Model for Teaching an LLB Program - Helen Saenger; Martin Hayden; Sam Garkawe; Jim Jackson (Legal Education Review)
In 1993 the Faculty of Law and Criminal Justice at Southern Cross University developed an innovative “block or “intensive teaching” model for the delivery of the first and second years of its three-year graduate LLB program. This model represented a significant departure from the standard format for the teaching of LLB programs in Australia. In this article, we report an evaluation of the effectiveness of the model. The results of the evaluation shed light on its potential strengths and weaknesses and provide insights into what some Australian law students value in teaching and program design. Although the block model was largely discontinued in 1996 for pragmatic reasons, it was generally found to have been a successful innovation. The findings from the evaluation should, therefore, be of considerable interest to other law schools, particularly those actively exploring options to increase their flexibility in program delivery. There is an emerging trend for law schools to offer Masters courses over short intensive teaching periods, and to offer LLB units (mainly later-year ones) during summer semesters within time frames that are more intensive than in the normal semester. Staff administering these courses should find the evaluation results especially relevant, particularly as the students undertaking the block program at Southern Cross University were all graduate students whose reactions to an intensive teaching program are more likely to be comparable with those of LLM and later-year LLB students.